Vitamin D Deficiency in a Cohort of Neapolitan Pregnant Women: Do We Really Live in the City of the Sun? - Laura Sarno; Annunziata Carlea; Serena Cabaro; Carmen Imma Aquino; Dalila Mantelli; Giuseppe Perruolo; Pietro Formisano; Maurizio Guida; Daniela Terracciano (IMR Press, 2023)
Background: Insufficient serum 25-hydroxyvitamin D [25(OH)D] levels are a global public health issue, and pregnant women are a significant at-risk group. We aimed to assess maternal serum 25(OH)D concentrations in a cohort of Neapolitan pregnant women and the association with dietary habits, to define which patients are at increased risk of hypovitaminosis and how we can identify them. Methods: This was a prospective observational study. We included 103 pregnant women attending a routine third trimester obstetric examination. Information on obstetrical history and socio-demographic characteristics were obtained through interviews and medical records. Vitamin D intake was assessed using a food frequency questionnaire. Serum 25(OH)D concentration was measured by DiaSorin Liaison and the cut-off value for deficiency was set at 20 ng/mL. Results: Among the 103 pregnant women recruited, 71 (68.9%) were Vitamin D deficient (mean value 12.6 ± 0.5 ng/mL). No statistically significant differences were found between the women involved in the study for: maternal age, pre-pregnancy body mass index (BMI), gestational weight gain, and gestational age at investigation. Women with hypovitaminosis reported a significantly lower intake of milk/yoghurt, cheeses/dairy products and fish. Maternal hypovitaminosis D significantly correlated with low birth weight. Conclusions: Our study confirms that Vitamin D deficiency is a common finding also in sunny areas. Patients with low level of Vitamin D reported a lower intake of food rich of this micronutrient. An accurate anamnesis can be an easy way to identify pregnant women at risk of hypovitaminosis D for whom screening and supplementation can be suitable.